Measurement of MMP Activity in Synovial Fluid in Cases of Osteoarthritis and Acute Inflammatory Conditions of the Knee Joints Using a Fluorogenic Peptide Probe-Immobilized Diagnostic Kit - Ryu, Ju Hee; Lee, Aeju; Huh, Myung Sook; Chu, Junuk; Kim, Kwangmeyung; Kim, Byung-Soo; Choi, Kuiwon; Kwon, Ick Chan; Park, Jong Woong; Youn, Inchan (IVYSPRING INT PUBL, 2012)
Purpose: A fluorogenic peptide probe-immobilized diagnostic kit was used to analyze MMP activity in the synovial fluids (SFs) from patients with osteoarthritis (OA) and acute inflammatory conditions of the knee joint. Methods: The MMP diagnostic kit containing a polymer-conjugated MMP probe immobilized on a 96-well plate was utilized for high-throughput screening of MMP activity in SFs from OA patients (n = 33) and patients with acute inflammatory conditions of the knee joint (n = 5). Results: Compared to SF from OA patients, SF from patients with acute inflammatory conditions of the knee joint presented stronger NIR fluorescent signals. In gelatin zymography, most samples from patients with acute inflammatory conditions of the knee joint also displayed 92 kDa (pro-form) MMP-9 and faint 84 kDa (active form) MMP-9, while SF from OA patients did not display detectable MMP-9 activity. Conclusion: The presence of a strong fluorescence signal from the MMP diagnostic kit corresponded well with patients with acute inflammatory conditions of the knee joint. The results suggest that our MMP diagnostic kit can be useful in differentiation between early stages of OA and acute inflammatory conditions of the knee joint.
Keywords: MATRIX-METALLOPROTEINASE ACTIVITY; DISORDERS; ARTHRITIS; DISEASE; MARKER; FORMS; SERUM